Revelations : a Blue Bloods novel / 3. - De la Cruz, Melissa, 1971- (De la Cruz, Melissa, 1971- Blue Bloods novel., 2008)
Schuyler Van Alen's blood legacy has just been called into question: Is the young woman in fact a Blue Blood, or is it the sinister Silver Blood that runs through her veins? When one of the Gates of Hell is breached by the Silver Bloods, the Blue Bloods will need Schuyler on their side.